Mobile visual searching method based on ascending extreme learning machine - Haiyang HU; Jun XU; Hua HU (Dianxin kexue)
Computer intelligence technology had been widely used in the field of image searching. Extreme learning machine has emerged as a new technology which overcomes the problems in traditional intelligent field and it has attracted more and more researchers. The algorithm performance of ELM was analyzed firstly，extending the method to image classification field. A basic mobile visual searching（BMVS）framework was proposed which applies ELM to image searching and optimizes the performance of ELM. Finally，the experiment proves the effectiveness of the method proposed by using ELM for the mobile vision searching. Through the experiments of comparison with SVM-based methods，the efficiency of the method proposed was also confirmed.